PLC Control System Implementation with IoT Based Industrial SCADA Development - Hendro Priyatman; Seno D. Panjaitan; Supriono; Muh. Revaldi Frizky (This journal is published by the Department of Electrical and Information Engineering, Faculty of Engineering, Universitas Gadjah Mada., 2025)
Control system challenges such as remote access and long-distance command execution can be addressed using supervisory control and data acquisition (SCADA) systems. SCADA enables real-time monitoring and control of industrial processes, allowing remote decision-making, improving operational efficiency, and accelerating response to issues. It also enhances data transparency, enabling engineers to detect and analyze failures more effectively. However, SCADA implementation often involves high costs and requires skilled personnel for maintenance. To address these limitations, this research developed an affordable SCADA system tailored for small and medium-sized industries. The system used a programmable logic controller (PLC) for control and a human machine interface (HMI) on the remote terminal unit (RTU). Data from the RTU were sent to a master terminal unit (MTU), which was independently developed and enabled remote monitoring and control via industrial internet of things (IIoT) technology using the message queueing telemetry transport (MQTT) protocol. The system monitored two variables: temperature (RTU 1) and rotational speed (RTU 2), aiming to measure communication time and data accuracy. Testing showed sensor accuracy of 98.6% for RTU 1 and 100% for RTU 2, with 100% communication accuracy between layers. The average real-time communication duration was 0.324 s, demonstrating high efficiency and low latency. These results indicate that an IoT-based SCADA system is reliable, cost-effective, and suitable for small to medium industrial applications. It is also easy to replicate and reconfigure, making it a practical solution for broader industrial adoption.